Short-term outcomes of percutaneous versus subcutaneous fascial flap fixation in cubital tunnel syndrome surgery: A retrospective cohort study - Tianyou Hu; Yujie Bian; Qiankun Wang; Tao Zhou; Hongxiang Zhou (Journal of Orthopaedic Surgery and Research)
Abstract Objective Percutaneous external suturing has been proposed as an alternative approach to fascial flap fixation during anterior subcutaneous transposition for cubital tunnel syndrome (CuTS), with the aim of minimizing deep tissue disruption and reducing postoperative complications. This study compared short-term outcomes between percutaneous external fixation and traditional subcutaneous fixation of fascial flaps in CuTS surgery. Methods In this retrospective cohort study, 114 patients who underwent anterior ulnar nerve transposition with fascial flap coverage were enrolled between January 2020 and December 2023. Patients were grouped based on the method of fascial flap fixation: subcutaneous (n = 57) or percutaneous (n = 57). Clinical assessments—including Visual Analog Scale (VAS), Patient-Rated Ulnar Nerve Evaluation (PRUNE), and Cubital Tunnel Syndrome Functional Score—along with nerve conduction studies (CMAP, SNCV, MNCV), were performed preoperatively and at 6-month follow-up. Results Compared to the subcutaneous group, the percutaneous group showed significantly greater improvement in VAS scores (VAS: -2.75 vs. -1.99, p < 0.001), PRUNE scores (PRUNE: -23.78 vs. -17.64, p < 0.001), and functional scores (Score: +3.58 vs. + 2.70, p = 0.0004). Increases in SNCV (16.45 m/s vs. 14.51 m/s, p = 0.035) and MNCV (18.55 m/s vs. 12.13 m/s, p < 0.001) were also more pronounced in the percutaneous group. Although CMAP improved in both groups, postoperative CMAP values were slightly higher in the subcutaneous group (6.02 ± 0.85 mV vs. 5.40 ± 0.51 mV, p = 0.002). No infections or wound complications occurred in either group; two reoperations for recurrent compression were required in the subcutaneous group. Conclusion Percutaneous external suturing may represent a safe and promising alternative for fascial flap fixation during CuTS surgery, with potential benefits in early postoperative pain relief, nerve conduction, and functional outcomes. However, longer-term studies are needed to assess durability and potential late complications. Trial registration This study was retrospectively registered with the Institutional Review Board of the First Affiliated Hospital of Anhui Medical University (Approval No. PJ2024-12-17).